Comparative proteomic analysis provides novel insights into the regulation mechanism underlying papaya (Carica papaya L.) exocarp during fruit ripening process - Bian Jiang; Siyan Ou; Ling Xu; Wanyi Mai; Meijun Ye; Haiping Gu; Tao Zhang; Changchun Yuan; Chenjia Shen; Jinxiang Wang; Kaidong Liu (BMC Plant Biology, 2019)
Abstract Background Papaya (Carica papaya L.) is a popular climacteric fruit, undergoing various physico-chemical changes during ripening. Although papaya is widely cultivated and consumed, few studies on the changes in metabolism during its ripening process at the proteasome level have been performed. Using a newly developed TMT-LCMS analysis, proteomes of papaya fruit at different ripening stages were investigated. Results In total, 3220 proteins were identified, of which 2818 proteins were quantified. The differential accumulated proteins (DAPs) exhibited various biological functions and diverse subcellular localizations. The KEGG enrichment analysis showed that various metabolic pathways were significantly altered, particularly in flavonoid and fatty acid metabolisms. The up-regulation of several flavonoid biosynthesis-related proteins may provide more raw materials for pigment biosynthesis, accelerating the color variation of papaya fruit. Variations in the fatty acid metabolism- and cell wall degradation-related proteins were investigated during the ripening process. Furthermore, the contents of several important fatty acids were determined, and increased unsaturated fatty acids may be associated with papaya fruit volatile formation. Conclusions Our data may give an intrinsic explanation of the variations in metabolism during the ripening process of papaya fruit.